Internet Addiction in Young Adults in Turkey: Loneliness and Virtual-Environment Loneliness - ÜMMET, DURMUŞ (TURKISH GREEN CRESCENT SOC, 2016)
The purpose of this research is to reveal the relationships in Turkey between young adults' loneliness in real life and loneliness in virtual environments, as well as to reveal the predictive effect of real-life and virtual loneliness on Internet addiction. The Internet Addiction, UCLA Loneliness, and Virtual-Environment Loneliness Scales were used in order to collect data. A total of 237 students, whose average age was 20.64 and were continuing their education at Marmara and Istanbul Medeniyet Universities, constituted the study group of the research. The statistical analyses that were performed showed a positive meaningful relationship for real-life loneliness with the Virtual Environment Loneliness Scale's sub-dimensions of virtual sharing and virtual socialization, and a negative meaningful relationship with its sub-dimension of virtual loneliness. According to the survey, real-life loneliness and virtual-environment loneliness (through all sub-dimensions) significantly predict Internet addiction in young adults (loss of control, tolerance development, and deterioration in social relations). Suggestions have been made through a discussion of the obtained findings related to the literature and other studies.
Keywords: Internet addiction; Addiction; Virtual environment loneliness; Loneliness; Young adults; ADOLESCENTS; VALIDITY; SCALE